Rapid and sensitive detection of ostreid Herpesvirus 1 in oyster samples by real-time PCR (Poster) - Pepin, Jean-francois; Riou, Antoine; Renault, Tristan (13th EAFP International Conference on 'Diseases of Fish and Shellfish', 2007)
Herpes and herpes-like virus infections have been reported in various marine mollusc species associated with high mortality rates. Following the characterisation and genome sequencing of ostreid herpesvirus 1 (OsHV-1), specific diagnostic tools have been developed based on conventional PCR techniques or in situ hybridisation. We have now developed a real-time PCR assay for rapid, sensitive and quantitative detection of OsHV-1, and compared it with a conventional PCR technique described previously. The new assay utilised SYBR® Green chemistry with specific primers C9/C10 targeting the C region, which is present in two copies in the OsHV-1 genome and encodes two proteins of unknown function. The assay was applied successfully to rapid diagnosis (100 minutes) of OsHV-1 in different developmental stages and tissue samples of Crassostrea gigas. This capability is important because no cell culture or in vitro system is available for quantitation of virus replication. The quantitative data that will emerge in future using the new assay will illuminate aspects of pathogenesis, in particular the viral loads in asymptomatic oysters and the kinetics of infection in specific target tissues. This poster presents real-time PCR assay and first data with field and experimental material.